1999
DOI: 10.1111/j.1540-8159.1999.tb00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proximal Ventricular Septal Pacing on Hemodynamics and Ventricular Activation

Abstract: Recently the use of alternate site pacing to improve cardiac function in patients with bradyarrhythmias has increased. In the present study, hemodynamics of right ventricular septal pacing were studied in seven dogs. A bipolar screw-in lead and endocardial lead were placed in the proximal right ventricular septum and right ventricular apex, respectively. The right ventricle was paced from each site. A conductance catheter and Millar catheter were inserted into the left ventricle to determine the left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…RV septal pacing is a more simple and feasible alternative permanent pacing site than LV‐based or biventricular pacing in patients with bradycardia 3 . Experimental studies 19–21 demonstrate that pacing at RV septal sites that are closer to the proximal portion of His bundle resulted in a shorter LV activation time and induced lesser disturbances on LV performances and structures. Furthermore, recent clinical studies 7,22–25 also suggest that pacing in the midseptal region of RV may lead to a lesser degree of abnormal LV electrical and mechanical activation, and thus can potentially avoid the adverse effects on LV function related to permanent RV apical pacing.…”
Section: Discussionmentioning
confidence: 99%
“…RV septal pacing is a more simple and feasible alternative permanent pacing site than LV‐based or biventricular pacing in patients with bradycardia 3 . Experimental studies 19–21 demonstrate that pacing at RV septal sites that are closer to the proximal portion of His bundle resulted in a shorter LV activation time and induced lesser disturbances on LV performances and structures. Furthermore, recent clinical studies 7,22–25 also suggest that pacing in the midseptal region of RV may lead to a lesser degree of abnormal LV electrical and mechanical activation, and thus can potentially avoid the adverse effects on LV function related to permanent RV apical pacing.…”
Section: Discussionmentioning
confidence: 99%
“…The differential effects of alternative RV pacing sites on QRS duration and ventricular systolic function have been studied in the past: Takagi et al 39 showed in a normal heart canine model that haemodynamics and interventricular conduction are less disturbed by proximal RV septal pacing than apical pacing. In contrast, Peschar et al 40 have demonstrated, also using a normal heart canine model, that although septal or apical LV pacing did not affect LV systolic function, RV septal pacing was not superior to RV apical pacing.…”
Section: Reversing the Deleterious Effects Of Rv Apical Pacing Alternmentioning
confidence: 99%
“…This observation has led to development of alternate pacing sites (right ventricular outflow tract (RVOT) or left ventricular (LV)) for electrical stimulation in patients with heart block and/or bradycardia [2], especially when congestive heart failure is present [5,6]. In spite of progress in evaluating myocardial function at the hemodynamic and electrophysiological levels [7][8][9], the influence of different pacing sites on the organized synchrony of contraction has not yet been defined.…”
Section: Introductionmentioning
confidence: 98%